RELATION BETWEEN THE INTENSITY OF THE SOUTH-WEST MONSOON AND THE OIL-SARDINE FISHERY OF INDIA - Murty, A V S; Edelman, M S (Indian Journal of Fisheries, 2011)
THE problem of fluctuations of marine fish populations and commercial stocks is a great concern of the marine fishery industries. The fluctuations depend upon the biological features of the individual species and the environmental factors. It is not possible to solve the problem without understanding both the aspects. The abundance of fish depends mainly upon the feeding conditions especially in larval and juvenile stages. And the feeding conditions depend upon the primary production which conditionally depends on the available nutrient salts in the sea. The availability of nutrients will much depend upon the vertical and horizontal circulations in the sea.